Multi drug resistant Pseudomonas aeruginosa in burn infection among Iraq patients: MDR Pseudomonas aeruginosa in burn infection - Jomaa Mohammed, Wasnaa; Mohammed, Hala (Cellular and Molecular Biology, 2025)
Pseudomonas aeruginosa is a prominent opportunistic pathogen, especially in burn wound infections, and is often associated with high morbidity and mortality due to its multidrug resistance (MDR) characteristics.This study aimed to evaluate the multidrug resistance profile and perform a molecular phylogenetic analysis of P. aeruginosa isolates recovered from human burn infection sample .Clinical specimens from burn wounds were subjected to traditional culture techniques and biochemical identification to isolate P. aeruginosa. The antibiotic susceptibility patterns were determined using the disc diffusion method according to CLSI guidelines. Molecular identification and phylogenetic characterization were performed using PCR amplification and Sanger sequencing of the 16S rRNA gene.The isolates demonstrated resistance to multiple antibiotics, notably cefixime and meropenem, indicating a multidrug-resistant phenotype. PCR confirmed the presence of P. aeruginosa through successful amplification of the 16S rRNA gene. Sequencing results and phylogenetic analysis revealed a high degree of genetic similarity between the local isolate and P. aeruginosa strains reported globally, suggesting potential international dissemination or conserved evolutionary patterns.